Implementation of Transformational Leadership and Professional Competence of the Principal at SMAN 3 Sawahlunto - Siskawati, Oies Febria; Asmendri, Asmendri; Gustina, Gustina (Indonesian Research Journal on Education, 2025)
This study explores the implementation of transformational leadership and the development of professional competence of the principal at SMAN 3 Sawahlunto. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation, with principals, teachers, administrative staff, students, parents, and supervisors as sources. The findings reveal that the principal applied transformational leadership through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Professional competence development was reflected in active participation in training, seminars, and initiatives to improve teacher professionalism. Supporting factors included teacher solidarity, staff support, student motivation, and collaboration with parents. Meanwhile, inhibiting factors comprised limited facilities and resistance to innovation. The study concludes that transformational leadership positively contributes to school quality improvement and professional development, affirming the relevance of Burns’ and Bass & Riggio’s transformational leadership theories in the Indonesian educational context.